ANTEGRADE PAPILLOTOMY WITH THE USE OF YAG:HO LASER IN STENOSIS OF THE MAJOR DUODENAL PAPILLA - N. V. Levchenko; V. V. Khrachkov; R. R. Shavaliev; D. P. Kislitsyn (Biomedical Photonics, 2018)
The purpose of our study was to develop and implement a new invasive method of papillotomy – an antegrade dissection of the major duodenal papilla using high-energy holmium (YAG:Ho) laser. Results of antegrade laser papillotomy in 35 patients are presented. All surgical procedures were laparoscopic, no indications for conversion were found. The use of high-energy holmium laser helps perform an adequate papillotomy with minimal damage to the surrounding tissues. Studies have shown that antegrade laser papillotomy is feasible in the presence of parapillary diverticula, severe deformity of the duodenum, and also when retrograde interventions are extremely difficult or impracticable. The high efficiency of the applied technique (in all cases the stenosis of the major duodenal papilla has been successfully eliminated) and the absence of complications and deaths is shown. Based on the analysis of the study results, a therapeutic algorithm for managing patients with stenosis of the major duodenal papilla is proposed.